Transcriptome Comparison Reveals the Adaptive Evolution of Two Contrasting Ecotypes of Zn/Cd Hyperaccumulator Sedum alfredii Hance - Yang, Qianying; Shohag, M. J. I.; Feng, Ying; He, Zhenli; Yang, Xiaoe (Frontiers in Plant Science, 2017)
Hyperaccumulating ecotype (HE) and non-hyperaccumulating ecotype (NHE) of Sedum alfredii Hance belong to the same species but exhibit contrasting characteristics regarding hyperaccumulation and hypertolerance to cadmium and zinc. The Illumina Hiseq 2500 platform was employed to sequence HE and NHE to study the genetic evolution of this contrasting trait. Greater than 90 million clean reads were obtained and 118,479/228,051 unigenes of HE/NHE were annotated based on seven existing databases. We identified 149,668/319,830 single nucleotide polymorphisms (SNPs) and 12,691/14,428 simple sequence repeats (SSRs) of HE/NHE. We used a branch-site model to identify 18 divergent orthologous genes and 57 conserved orthologous genes of S. alfredii Hance. The divergent orthologous genes were mainly involved in the transcription and translation processes, protein metabolism process, calcium (Ca2+) pathway, stress response process and signal transduction process. To the best of our knowledge, this is the first study to use RNA-seq to compare the genetic evolution of hyperaccumulating and non-hyperaccumulating plants from the same species. In addition, this study made the sole concrete for further studies on molecular markers and divergent orthologous genes to depict the evolution process and formation of the hyperaccumulation and hypertolerance traits in S. alfredii Hance.